Tingkeban: Ritual Orang Jawa Dalam Masa Kehamilan di Kalisari, Bojonegoro, Jawa Timur - Austiyana, Mimin (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2021)
Pregnancy is viewed as very important event for Javanese people, because being pregnant is a sign of fertility,especially a male child, is viewed as an increase in wealth. A woman with many children is envied; a barren woman is pitied (Geertz 1961:8), and having a baby is considered as necessary for creating a complete and perfect houshold and family. Pregnancy is also seen as potentially dangerous in Javanese society, and it involves a wide array of indigenous beliefs and practices to the periods of pregnancy. Therefore, this study explored perception, meanings and practices related to pregnancy of the people in Kalisari, Bojonegoro, East java. The focus of the study will examine rites of passage performed during pregnancy. This study is a descriptive study and attempt to give a clear picture of the problem. The study is of a qualitative nature, and it showed that pregnancy period can be analyzed as important rite of passage or period of transition. When a woman publicly announces her pregnancy a ceremony is held (tingkeban) which symbolizes the separation of the woman from her previous status.